Best Answer

26 = -6y + 6 + 2y = -4y + 6

Subtracting 6 from both sides: 20 = -4y

Dividing both sides by (-4): -5 = y

Q: What is the answer to 26 equals -6y plus 6 plus 2y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9y-3y=6y; 6y+2y=8y; so your answer is 8y

6y equals 5y plus 2y can be simplified to 6y = 7y. To solve for y, subtract 7y from both sides of the equation, which gives 6y - 7y = 0. This simplifies to -y = 0, or y = 0.

(3, 3)

x = -4 and y = 4

6y + (2-2)y = 6y 6(5) + (2-2)5 = 6(5) 30 + 0 = 30

Related questions

6y

9y-3y=6y; 6y+2y=8y; so your answer is 8y

-6y + 14 + 4y = 32-2y = 32 - 14-2y = 18y = - 9

6y equals 5y plus 2y can be simplified to 6y = 7y. To solve for y, subtract 7y from both sides of the equation, which gives 6y - 7y = 0. This simplifies to -y = 0, or y = 0.

(2, 1)

(3, 3)

x = -8, y = 10

(3,3)

x=6y-4x=-2y+28Substitute (6y-4) for x in the second equation and solve for y:6y-4=-2y+288y=32y=4Then solve for x:x=6(4)-4=20(20,4)

x = -4 and y = 4

6y + (2-2)y = 6y 6(5) + (2-2)5 = 6(5) 30 + 0 = 30

10y = 2y - 6y + 7 10y =-4y + 7 10y +4y = 7 14y = 7 y = 1/2 = .5